AKIBAT HUKUM PEMBATALAN PERKAWINAN CAMPURAN OLEH PENGADILAN KARENA MENGGUNAKAN DOKUMEN YANG TIDAK SAH (Studi Putusan Pengadilan Negeri Jakarta Selatan No. 586/Pdt.G/2014) - MUTIA RAMADANI (PREMISE LAW JURNAL, 2017)
Mixed marriage, according to Law No. 1/1974 on Marriage, is a marriage between an Indonesian and a foreigner and both of them live in Indonesia. In a mixed marriage, both of them have to provide letters and documents which are concerned with the requirements for a mixed marriage according to legal provisions. The research used judicial normative and descriptive analytic method by analyzing legal provisions on marriage in general and mixed marriage in particular. The result of the research shows that a mixed marriage which has incomplete documents is legally defective and vulnerable to be sued for cancelling it to the court by the parties concerned. The Panel of Judges’ legal consideration at the Jakarta District Court in cancelling the marriage between Jessika Iskandar and Ludwig Franz Willibald in the Verdict No. 586/PDT.G/2014/PN Jaksel was that the marriage used illegal documents or it was contrary to legal provisions in mixed marriage so that the judges had reasonable decision to cancel it. Keywords: Cancellation, Mixed Marriage, Illegal Documents